Patterns of Use in Transesophageal Echocardiography for Liver Transplantation: A Systematic Review. (December 2022) - Dunkman, W. Jonathan; Manning, Michael W.; Williams, David A.
Transesophageal echocardiography is frequently but not always used to guide anesthetic management during liver transplantation. We performed a systematic review of the literature to identify and summarize any studies reporting on the frequency and characteristics of TEE use for liver transplantation. Studies were identified by searching several relevant terms on PubMed and citation searching of relevant reviews. We identified 5 studies reporting the results of surveys performed between 2003 and 2018. Use of TEE for liver transplantation increased from 11.3% of centers in 2003 to greater than 90% of centers by 2014 and 2018. Only 38%–56% of centers use it routinely with the rest using it only in special circumstances. About a third of centers usually perform a comprehensive exam, with the majority performing a more limited exam based on the needs of the case. Use of TEE for liver transplantation is common but not universal. This review summarizes the current knowledge about the frequency and circumstances of use, but there is an opportunity for further systematic study and discussion.